Reconstruction of potential function for Sturm-Liouville operator with Coulomb potential - Panakhov, Etibar S.; Sat, Murat (Springeropen, 2013)
In this paper, we are concerned with an inverse problem for the Sturm-Liouville operator with Coulomb potential using a new kind of spectral data that is known as nodal points. We give a reconstruction of q as a limit of a sequence of functions whose nth term is dependent only on eigenvalue and its associated nodal data. It is mentioned that this method is based on the works of Law and Yang, but we have applied the method to the singular Sturm-Liouville problem.
Keywords: Coulomb potential; nodal point; reconstruction formula